Diffusion Tensor Tractography Studies on Injured Anterior Cingulum Recovery Mechanisms: A Mini-Review - Jang, Sung Ho; Seo, Jeong Pyo (Frontiers in Neurology, 2018)
The cingulum, a major structure in the limbic system, contains the medial cholinergic pathway, which originates from the basalis nucleus of Meynert (Ch 4) in the basal forebrain. The cingulum is involved in various cognitive functions, including memory, attention, learning, motivation, emotion, and pain perception. In this mini-review, ten studies reporting on recovery mechanisms of injured cinguli in patients with brain injury were reviewed. The recovery mechanisms of the injured anterior cinguli reported in those ten studies are classified as follows: Mechanism 1, recovery via the normal pathway of the cingulum between the injured cingulum and Ch 4; mechanism 2, recovery through the neural tract between the injured cingulum and the brainstem cholinergic nuclei; mechanism 3, recovery via the lateral cholinergic pathway between the injured cingulum and the white matter of the temporo-occipital lobes; mechanism 4, recovery through the neural tract between the contralesional basal forebrain and the ipsilesional basal forebrain via the genu of the corpus callosum; and mechanism 5, recovery through the neural tract between the injured cingulum and Ch 4 via an aberrant pathway. Elucidation of the recovery mechanisms of injured anterior cinguli might be useful for neurorehabilitation of patients with anterior cingulum injuries. Diffusion tensor tractography appears to be useful in the detection of recovery mechanisms of injured anterior cinguli in patients with brain injury. However, studies on cingulum injury recovery mechanisms are still in the early stages because most of the above studies are case reports confined to a few brain pathologies. Therefore, further studies involving large numbers of subjects with various brain pathologies should be encouraged. In addition, studies on the influencing factors and clinical outcomes associated with each recovery mechanism are warranted.